“expressive Rationality”: Habitus And Field In A Malaysian Cosplay Community - Chan, Rachel Suet Kay (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Malaysian cosplayers, as a subset of Asian cosplayers, engage in a visually performative activity which raises the issues of ethnic and gender performativity, among other identity markers. This is further contextualised within an “everydaydefned” experience of identity, in which its formation is inﬂuenced by non-“social power” agents such as popular narratives (Baharuddin 1996: 18; Baharuddin and Athi 2015: 268). In addition, cosplayers are noted to be affected by global cultural ﬂows. Given its relevance to studies of cosplay, I use Bourdieu’s framework of cultural capital to outline the components which make up an established cosplayer. Using a snowball sample, I survey several tertiary educated and employed Malaysian cosplayers regarding the cultural capital they use to navigate the intersections of race/ethnicity, gender, and socioeconomic status. I compare the responses of my sample to that of cosplayers from international forums, and to the content of emerging counter-hegemonic popular narratives. My fndings suggest that cosplay can be viewed as a form of public theatre, comprising rational and expressive elements.